THE REVIEW OF HIGH-QUALITY EDUCATION IN THE DIGITAL ERA: EMPLOYING APPLICATIONS AS LEARNING MEDIA IN RELEVANT RESEARCH - Aris, Affandy Agusman; Feriyanti, Yang Gusti; Lutfi, Nafisatul; Utami, Agnes Nora Eko Wahyu; Murthada, Murthada (Consilium: Education and Counseling Journal, 2024)
The paper aims to investigate high-quality education in the digital era: the use of applications as learning media in relevant research. Judging from its type, this research is literary in nature, including the type of library research. Library research is research in which data collectionsis carried out by collecting data from various literature. The literature studied is not limited to bookssbut can also include documentation materials, magazines, journalssand newspapers. Advances in communication technology havesinfluenced many people's views on things in everyday life, including views on parenting. Parents used to allow their children to play traditional games with other children outside. However, parents are currently relying more on digital technology as a gaming medium for their children. Education in the digital age is education that must integrate information and communication technology into all subjects. Currently, information and communication technology, including smartphone technology, is developing very rapidly. Smartphones come with different operatingssystems, and one of the most popular operating systems currently is Android. Android is an operating system based on open source. The Androidsoperating system, with its diverse application development, can create representative learning media. With Android-based technology, learning is no longer monotonous with text, but audio or visual elements or even animations can be created to help students understand the material.